Globalization, Citizenship and Subjectivity: An analysis of the changes in the last five generations in my family - Gyawali, Sindhu (Nepal Journal of Multidisciplinary Research, 2023)
Human Subjectivities are shaped by one’s social position and practices in the social field. Subjectivities may be durable, but they are changeable. The subjectivities one carries may differ from generation to generation. What I perceive about myself is different from what my parents perceived and what my grandparents perceived and how they developed their subjectivities. We have to see these human subjectivities across time and space. This paper explores the interplay of local, national and global social fields in forming subjectivity and in analyzing the changes in the last five generations in my family. I began my study by looking at the genealogy of Gyawali family. I approached the emergence of such changes through the theoretical lens of Bourdieu, Foucault, and Anderson. As the research problem I wanted to investigate was of a historical nature, the methods that I could choose were already conditioned by that. I picked up oral history research, and biographical interviews as two basic research methods. The changes in the way of life in my family due to such fields can be seen directly in the economy, use of technology, way of life and ultimately in the culture. When we entered into the globalization process the traditional norms and values of the family have transformed with the global way of life. We are becoming more self-reliant and empowered but at the same time, it has also created mental anxiety and stress. New subjectivities and identities have emerged in the last five generations in my family.